Recurrent spinal bifida prevention and folic acid use (2021)
Background: Spinal bifida (SB) is a disabling congenital abnormality with folic acid (FA) deficiency, recognized as a predisposing factor. Existing literature reports reduction in its incidence following peri-conceptual supplementation with Folic acid. However, there is limited literature on maternal subsequent pregnancy following SB occurrence with regards to awareness and usage of folic acid supplementation and dietary consumption of folate in our local environment. Materials and Methods: A cross-sectional study on the awareness and practice of peri-conception FA supplementation among mothers with children affected with SB, in affected and subsequent pregnancy, was done. Data was obtained using an interviewer-administered questionnaire with analysis done with descriptive analysis. Results: There were 12 respondents with majority of them (91.7%) less than 30 years old at the time of their first pregnancy and the mean of current age was 24.8 + 1.3 years. While just 2(16.7%) used FA in the pre-conception period in the SB pregnancy, only eight (66.7%) of the mothers used FA in the pre-conception period of the subsequent pregnancy despite increased awareness from 8(66.7%) to 12(100%). The dietary consumption of folate rich food was poor. Subsequent pregnancies were planned and there was no recurrence Conclusions: Improvement in the peri-conceptual usage of folic acid in mothers with a child previously affected with SB and no recorded recurrence. National policies on folic acid supplementation and pre-conceptual care have been further validated.